Integrasi Ilmu Agama-Sains Badiuzzaman Said Nursi dan Relevansinya dengan Pendidikan Agama Islam Era Digital di Indonesia - Himmawan Ayathurrahman; Sadam Fajar Shodiq (Bulletin of Indonesian Islamic Studies, 2023)
The integration of religion and science is an interesting topic for discussion. Until now the debate on the legitimacy of the integration of religion-science is still being carried out by scholars. This article discusses the integration of religion and science from the perspective of Bediuzzaman Said Nursi and how relevant it is in the Digital Age of Islamic Religious Education in Indonesia. This study uses a qualitative method with the type of library research. This study analyzes the content of Said Nursi's thoughts from various works of literature. The results of the study show that there is relevance to Said Nursi's thoughts which are based on the integration of knowledge rooted in human nature to seek true happiness in this world and the hereafter. Said Nursi's thoughts are considered relevant for the development of the context of Islamic Religious Education in the digital era in Indonesia which includes strengthening religious-spiritual in the digital era, strengthening the integration of religion-science initiated by the Indonesian Ministry of Religion, enriching learning methods in the digital era, deepening curriculum reform and 21st-century skills, revitalization of moral education in the digital era and ethics in learning.